Challenges and Breakthroughs: The Digital Transformation of Aesthetic Education in Higher Education (Journal of Global Arts Studies, 2025)
Background： With the rapid advancement of information technology, aesthetic education in higher education is undergoing a profound digital transformation. This transformation not only reshapes instructional methodologies but also exerts a significant influence on pedagogical paradigms and students' aesthetic development. Objective： This  study aims to  explore the necessity  of digital transformation in aesthetic  education within higher education, examine the existing challenges, and propose viable pathways for overcoming these difficulties to foster high-quality development in aesthetic education. Methods： This study investigates the digital transformation of aesthetic education in higher education through literature review  and  case  study  analysis.  It  explores  the  challenges  of integrating  digital  technologies  into teaching and examines the interplay between technological tools and educational goals. Results： The paper proposes five strategic measures: building a systematic instructional framework, integrating AI to enhance teaching, encouraging interdisciplinary collaboration, innovating teaching methods, and fostering digital citizenship. These aim to improve the quality and relevance of aesthetic education in the digital era. Conclusion： The study highlights the significant impact of digital technologies on pedagogical models and educational   philosophy.   It   contributes  to  both  theoretical   and  practical  discussions   on  the   sustainable development of aesthetic education and offers insights for future innovation.
Keywords: Aesthetic Education in Higher Education; Digital Transformation; Technology Applications; Educational Innovation